Lenticulostriate Artery Aneurysm: 2-Dimensional Operative Video. Issue 2 (23rd November 2019) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Saccular aneurysms that arise from the origin of or along a lenticulostriate artery are rarely observed. In general, occlusion of the lenticulostriate artery is discouraged because of the risk of a capsular infarction. This patient was a woman with moyamoya disease who demonstrated a fusiform aneurysm of a lenticulostriate artery. Image guidance was critical to correctly identify the location of the aneurysm. The lenticulostriate artery was occluded by a surgical clip to obliterate the aneurysm and consequently the flow through the artery. However, the patient tolerated the procedure well and did not experience an ischemic stroke from the vessel occlusion. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona.